Bilingual children with language impairment: A comparison with monolinguals and second language learners - GUTIÉRREZ-CLELLEN, VERA F. (2007)
The purpose of this study is twofold: (a) to examine whether English finite morphology has the potential to differentiate children with and without language impairment (LI) from Spanish-speaking backgrounds and different levels of English proficiency in comparison to Hispanic English speakers and (b) to investigate the extent to which children who are bilingual exhibit differences in their grammatical performance because of cross-linguistic influence from their first language. Seventy-one children between the ages of 4 years, 5 months and 6 years, 5 months were distributed into the following five groups: English as a first language (EL1) speakers with typical language development (TLD), EL1 speakers with LI, Spanish–English bilinguals with TLD, Spanish–English bilinguals with LI, and English as a second language (EL2) learners with TLD were compared on regular verb finiteness and nominative subject use using spontaneous narrative samples. The EL1 children with LI had significantly lower verb accuracy rates than the EL1 controls with TLD. Verb finiteness marking was also a significant discriminator for the bilinguals with LI. There was no evidence of cross-linguistic influence, however. The analysis indicated no significant differences between EL1 and bilingual children on subject or verb use. The EL2 group only presented difficulties with finite verb use. The typological differences between English and Spanish for overt subject use did not seem to affect the performance of either typical or atypical bilingual learners. The findings underscore the need for addressing language dominance in future bilingual studies.